Design of low ground sampling distance (GSD) imaging system payload for 1U-sized CubeSat application / Fatimah Zaharah Ali - Ali, Fatimah Zaharah (2023)
The attributes of 1U CubeSat which are small mechanical size, light in weight, and low power supply, have been the constraints for selecting an imaging mission system. As the result, 1U CubeSat is usually attached with an imaging sensor that suits based on its limitations without putting the high-resolution imagery as a vital consideration. Imaging system with high number of pixels that produces high resolution imagery requires high power and usually comes in bigger size due to the outrages processing requirements. To solve the issue, an imaging system with high ground resolution that is associated with low ground sampling distance (GSD) was designed to be practical for the application of 1U CubeSat. To strategize the design and development of the imaging system, the main components of the imaging system were optimally and feasibly chosen based on 1U CubeSat's derived limitations, followed by selection of suitable optical device with longer focal length that contributed to lower GSD value, and verification of space application and imagery output in terms of GSD. As the BIRDS CubeSats Project was considered as reference for its space heritage, the space application was set at 380 to 400 km working distance, and thus, 16 m GSD imagery was acquired when the selected 5 MP CMOS imaging sensor was applied with 35 mm focal length lens. The result led to the small swath area that allowed the imaging sensor to focus on the small element of the target area. The functionality, integration, and space environment tests were successfully performed to ensure the develop imaging mission system was qualified for space application. As for imagery validation through RGB and SNR analysis, it showed that the distribution of red colour decreased including the SNR with the implementation of IR Cut Filter that removed IR ray from entering the imaging sensor. This research proved that lU-sized CubeSat was capable of having a high ground resolution imaging system when the GSD was reduced through the focal length of the optical lens. The works have contributed to the multination collaborative ASEANSAT project which was the continuation of 1U CubeSat development in Malaysia.